Detection of TLS plantlets of oil palm using specific grda markers via pcr approach - Wong, Connie Ting Ting (2015)
Truncated Leaf Syndrome (TLS) abnormality is one of the obstacles in the oil palm tissue culture as it is only observable after transferring to nursery which gives a drawback as it consumes a lot of time, expenses and labour. Therefore, early detection of the TLS plantlets while it is still in culture can save money, time and labour. This study aimed to investigate whether a previously isolated genomic RDA DNA marker can be used to distinguish TLS plantlets from normal plantlets. DNA extraction was carried out on leaves of five unknown clones and two known clones of normal and TLS plantlets using the modified method of Dellaporta. Smeared bands observed in the five unknown samples indicated degradation of DNA or low DNA quality which resulted from the poor sample quality, whereas samples from clones FC6432 and FC6516 showed a better DNA quality. The expected PCR product of 500 base pairs was successfully amplified using forward and reverse 1181BgI primers in all the tested samples. The amplified PCR product will have to be verified by Southern analysis or sequencing. Time constraints limited the continuation of the southern analysis. Based on PCR results, this marker was not able to differentiate the four known plantlets since the expected bands were present both in the TLS and normal plantlets of clones FC6432 and FC6516. Hence, the 1181BgI primers are not suitable to be used as the DNA marker for detecting TLS plantlets.